ANALISIS TINGKAT KEPENTINGAN DAN KINERJA (IMPORTANCE-PERFORMANCE ANALYSIS) NILAI KEGUNAAN APLIKASI M-COMMERCE - Elyasa, Fatiya Rahmita; Sugito, Sugito; rusgiyono, agus (Jurnal Gaussian, 2024)
Good application quality can bring user satisfaction to form user’s loyalty and trust in the company. The level of user satisfaction is different between Gojek and Grab even though each them has similarities in application features. Gojek and Grab are trying to make position as the most popular by the community in getting people's needs quickly and efficiently with huge competitive. This study aims to analyze and compare the usability qualities of Gojek and Grab based on the User Experience Questionnaire (UEQ) approach on the dimensions of attractiveness, perception, efficiency, dependability, stimulation and novelty. Measurements are made using Importance-Performance Analysis to graphically measure customer satisfaction so that service quality improvement priorities can be established. The data was collected by questionnaire to 32 selected respondents who accessed the Gojek and Grab applications in the Greater Jakarta area in August-December 2022. Based on the results of the study, the position of the usability quality attributes in Gojek and Grab was visually almost the same for each IPA quadrant. The Gojek application is superior in 5 dimensions to Grab, in terms of attractiveness, perception, dependability, stimulation, and novelty. Grab has one dimension that is superior to Gojek, in terms efficiency.